The effect of fiber supplementation on the prevention of diarrhea in hospitalized patients receiving enteral nutrition: A meta-analysis of randomized controlled trials with the GRADE assessment - Kaewdech, Apichat; Sripongpun, Pimsiri; Wetwittayakhlang, Panu; Churuangsuk, Chaitong (Frontiers in Nutrition, 2022)
Introduction: There are various advantages of enteral nutrition (EN) in hospitalized patients. However, post-feeding diarrhea has been seen frequently and has been linked to negative outcomes. The EN formula itself may have an impact on how diarrhea develops, and theoretically, fiber supplements may help patients experience less diarrhea. Our aim was to thoroughly evaluate whether adding fiber to the EN decreases the likelihood of developing diarrhea and whether different fibers pose different effects on diarrhea. Methods: We conducted a meta-analysis on fiber supplementation in hospitalized adult patients receiving EN. We thoroughly searched the Medline, Embase, Scopus, Web of Science, CENTRAL, and ClinicalTrials.gov from inception to 1st September 2022. Only randomized controlled trials (RCT) were included. The pooled results on diarrhea incidence were calculated using a random-effects model. GRADE approach was applied. Only the fiber types from the soy polysaccharides (Soy, n=4), psyllium (n=3), mixed soluble/insoluble (Mixed fiber, n=3), pectin (n=2), and partially hydrolyzed guar gum (PHGG, n=2) were examined in the sensitivity analysis. Results: Among 4,469 titles found, a total of 16 RCTs were included. Overall, compared to fiber-free formulas, fiber supplementation reduced the occurrence of diarrhea in patients receiving EN by 36% (pooled risk ratio [RR] of 0.64 [95%CI: 0.49-0.82, p=0.005; I2=45%]), with the GRADE evidence of moderate certainty. Only Mixed fiber and PHGG significantly decreased the diarrhea incidence according to the sensitivity analyses for fiber types (RR 0.54, 95%CI: 0.39-0.75, I2=0% and RR 0.47, 95%CI: 0.27-0.83, I2=0%, respectively). Results for the remaining fiber types were unclear. Conclusion: According to meta-analysis, in hospitalized patients receiving EN, fiber supplements help lessen post-feeding diarrhea. However, not all fiber types produced successful outcomes. Diarrhea was significantly reduced with PHGG and mixed soluble/insoluble fiber.